Performance evaluation and prediction of the integrated circuit industry in China: A hybrid method. (March 2020) - Zhou, Xiaoyang; Chen, Hao; Chai, Jian; Wang, Shouyang; Lev, Benjamin
Abstract: Since the "ZTE ban", the development of the integrated circuit (IC) industry has attracted wide attention, especially in China. The performance evaluation and prediction of the IC industry is of great significance for promoting the development of this industry. In this paper, a hybrid method is proposed to study the performance of the IC industry from the perspectives of evaluation and prediction, which is unique as it evaluates the performance at past, current and future terms simultaneously. Firstly, a dynamic data envelopment analysis model is used to explore the performances of the IC industry between China and the United States from 2008 to 2017. Furthermore, in order to figure out the main sources of the inefficiency, the projection analysis is implemented based on the performance scores. Then, the grey model GM(1, 1) is employed to predicted the performance of China's IC industry from 2018 to 2022, so as to point out the progressive direction for the future development of the industry. The empirical results show that: (1) as far as performance is concerned, there is a significant gap between China and the United States in the IC industry during 2008–2017, among which the most obvious gap is occurring in "IC packaging & testing", followed by "IC design" and "wafer fabrication"; (2) the primary cause of the low performance in China's IC industry is the redundancy of the inputs, especially in "IC packaging & testing", and the redundancy problem of labour investment is found to be the most serious; (3) according to the predicted results, the IC industry in China will steadily increase in terms of the performance scores in general, and the performance improvement of "IC packaging & testing" is relatively obvious, while the other two categories have a slight range of growth. Finally, the policy implications of improving the performance of the IC industry are put forward. Highlights: Develop a hybrid method to evaluate the performance at past, current and future terms, simultaneously. Evaluates and analyzes the performance of the IC industry in China and the United States during 2008–2017. Identifies the sources of operational inefficiency of the IC industry by a projection analysis. Predicts the performance of the IC industry in China from 2018 to 2022.